Digital Da’wah as Soft Power: A Conceptual Review of Islamic Communication in Contemporary Global Politics - Nanda Khairiyah; Badrah Uyuni; Yanuardi Syukur (ISTIFHAM, 2025)
Digital technologies have transformed Islamic communication by expanding da’wah beyond localised religious preaching into transnational digital spaces where religious narratives intersect with global cultural and political perceptions. While existing studies have examined digital da’wah primarily as a pedagogical, sociological, or media phenomenon, its potential role as a source of attraction-based influence remains underexplored. This study addresses this gap by conceptualising digital da’wah as a form of Islamic soft power operating within contemporary digital environments. Using a qualitative literature review and conceptual synthesis, the article integrates soft power theory with scholarship on digital Islamic communication, religious moderation, and platform governance. The analysis develops a conceptual model that illustrates how platform dynamics mediate digital da’wah narratives, as interpreted through audience reception and translated into soft power outcomes such as cultural attractiveness, moral legitimacy, and narrative influence. The findings demonstrate that moderation-oriented digital da’wah, when supported by ethical credibility and algorithmic visibility, contributes to shaping global perceptions of Islam through non-coercive means. This study advances theoretical discussions by positioning digital religious communication as a legitimate domain of soft power analysis and offers a framework for examining religion’s role in global symbolic politics.